Synthesis and In Vitro Characterization of Novel Dextran-Methylprednisolone Conjugates with Peptide Linkers: Effects of Linker Length on Hydrolytic and Enzymatic Release of Methylprednisolone and its Peptidyl Intermediates - Penugonda, Suman (2008)
To control the rate of release of methylprednisolone (MP) in lysosomes, new dextran-MP conjugates with peptide linkers were synthesized and characterized. Methylprednisolone succinate (MPS) was attached to dextran 25 kDa using linkers with 1–5 Gly residues. The release characteristics of the conjugates in pH 4.0 and 7.4 buffers, blood, liver lysosomes, and various lysosomal proteinases were determined using a size-exclusion and/or a newly-developed reversed-phase HPLC method capable of simultaneous quantitation of MP, MPS, and all five possible MPS-peptidyl intermediates. We synthesized conjugates with ≥ 90% purity and 6.9–9.5% (w/w) degree of MP substitution. The conjugates were stable at pH 4.0, but released MP and intact MPS-peptidyl intermediates in the pH 7.4 buffer and rat blood, with faster degradation rates for longer linkers. Rat lysosomal fractions degraded the conjugates to MP and all the possible intermediates also at a rate directly proportional to the length of the peptide. Whereas the degradation of the conjugates by cysteine peptidases (papain or cathepsin B) was relatively substantial, no degradation was observed in the presence of aspartic (cathepsin D) or serine (trypsin) proteinases, which do not cleave peptide bonds with Gly. These newly-developed dextran conjugates of MP show promise for controlled delivery of MP in lysosomes.